Erratum. (September 2013) - Unknown
Volume 41, issue 6, page 666 "Mapping the 'forbidden zone' near and away from the fixation point" by Ashley Chung-Fat-Yim, Hiroshi Ono In the results and discussion section of experiment 1, table 1 reported the standard deviation associated with the arithmetic mean and not the standard deviation associated with the geometric mean. Table 1 below includes the correct geometric standard deviation of each condition. Table 1. The critical disparity gradient calculated from the geometric mean of the disparity gradient (GMDG) values and variability (SD) of the geometric mean. The critical disparity gradient calculated from the geometric mean of the two slopes (GMTS) of the lines of best fit and the goodness of fit (R 2 ). Stimulus situation Participant YC AC MS FZ Central Fixation/Central Inducer GMDG (SD) 0.11 (1.39) 0.17 (1.23) 0.12 (1.40) 0.10 (1.36) GMTS of Best Fit Line (R 2 ) 0.12 (0.93) 0.16 (0.99) 0.11 (0.99) 0.11 (0.94) Peripheral Fixation/Peripheral Inducer* GMDG (SD) 0.11 (1.49) 0.13 (1.60) 0.08 (1.27) 0.14 (1.45) GMTS of Best Fit Line (R 2 ) 0.12 (0.90) 0.14 (0.99) 0.07 (0.99) 0.15 (0.91) Central Fixation/Peripheral Inducer* GMDG (SD) 0.13 (2.45) 0.19 (1.61) 0.21 (1.87) 0.14 (2.05) GMTS of Best Fit Line (R 2 ) 0.10 (0.89) 0.13 (0.94) 0.18 (0.83) 0.12 (0.87) Note. Combined disparity gradient values from stimulus situations where the inducer pin was located 10° to the left and 10° to the right of the median plane. * No variability among ratios is indicated by the standard deviation of unity.